Insights Into Detecting Adult ADHD Symptoms Through Advanced Dual-Stream Machine Learning - Christian Nash; Rajesh Nair; Syed Mohsen Naqvi (IEEE, 2024)
Advancements in machine learning offer promising avenues for the identification of ADHD symptoms in adults, an endeavour traditionally encumbered by the intricacies of human behavioural patterns. In this paper, we introduce three innovative dual-stream models. The proposed approach utilises a novel multi-modal dataset recorded for ADHD symptoms detection, leveraging RGB video alongside facial, body posture and hand landmark data. The fusion of these different sub-modalities within video enhances the discriminative capability of the ADHD symptoms detection system. A primary objective was to maintain minimal model depth while achieving competitive performance. Through randomised search cross-validation and a rigorous leave-one-out validation scheme, the proposed model achieves high generalisability and robust symptom identification, suggesting strong potential for application in clinical environments. Evaluation boasts the state-of-the-art performance of the proposed model, demonstrating an accuracy of 98.67%, a precision of 98.01%, and a recall of 98.88%. These metrics attest to the model’s ability to consistently identify ADHD symptoms while maintaining a minimal parameter footprint. This delicate balance provides a significant step forward in behavioural health analytics.